2009
DOI: 10.1007/s11747-008-0130-0
|View full text |Cite
|
Sign up to set email alerts
|

Technology readiness and usage: a global-identity perspective

Abstract: The past several decades have witnessed the rapid globalization of consumption markets and widespread diffusion of information and communication technologies. However, the use of technology by consumers is not a foregone conclusion. We investigate the role of global self-identity on the orientation toward technology readiness and usage. Relying on a social-identity model of motivation as our theoretical framework, we propose a model which incorporates global self-identity (i.e., cosmopolitanism/parochialism an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 80 publications
4
76
0
6
Order By: Relevance
“…Each dimension of TRI accounts for four to five items. In line with past research, we created a composite readiness index based on averages of each dimension (Westjohn et al 2009;Walczuch Lemmink, and Streukens 2007).…”
Section: Technology Readinessmentioning
confidence: 99%
“…Each dimension of TRI accounts for four to five items. In line with past research, we created a composite readiness index based on averages of each dimension (Westjohn et al 2009;Walczuch Lemmink, and Streukens 2007).…”
Section: Technology Readinessmentioning
confidence: 99%
“…al, 2010). Many studies have been carried out to test relationships between technology readiness and different variables such as cosmopolitanism, global identification, promotion focus, prevention focus (Westjohn et al, 2009) H1: There is difference between male and female in terms of purchasing items through the internet.…”
Section: Literaturementioning
confidence: 99%
“…It has impacts on consumer satisfaction and service quality Dabholkar 1991;Meuter et al 2000). TR is also a determinant of technology adoption and usage (Davis 1989;Davis et al 1989;Elliott et al 2008;Koufaris 2002;Lam et al 2008;Liljander et al 2006;Lin and Hsieh 2006;Massey et al 2007;Niehm et al 2010;Westjohn et al 2009). Liljander et al (2006) found that customer attitude, adoption, and evaluation were only slightly affected by technology readiness.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%